Integrating Dense Genotyping with High‐Throughput Phenotyping Empowers the Genetic Dissection of Berry Quality and Resilience Traits in Grapevine - Zhang, Yuyu; Wang, Yongjian; Henke, Michael; Carbonell‐Bejerano, Pablo; Wang, Zemin; Bert, Pierre‐François; Wang, Yi; Li, Huayang; Kong, Junhua; Fan, Peige; Dai, Zhanwu; Liang, Zhenchang (Advanced science, 2025)
Investigating the genetic architecture of important agronomic traits in grapevine, like berry quality and resilience to abiotic stress, has been hampered by bottlenecks in genotyping and phenotyping. To address these limitations, this study aimed to develop innovative tools to unravel the complex polygenic genomic architecture of these traits. Specifically, a high‐density 200K single nucleotide polymorphism array is developed and validated its effectiveness by genotyping 471 accessions from three F1 breeding populations. A high‐throughput grape phenotyping tool is developed to accurately capture berry color, shape, and size. By integrating data from the two platforms, associated loci are identified over three growing seasons. Association mapping and haplotype analysis identified novel loci and candidate genes for berry shape (bHLH017), soluble sugars (ACT), and organic acids (ALMT1 and FUSC2), as well as vine cold tolerance (NAC08), and fine‐mapped the flower sex determination locus. Furthermore, the functional role of NAC08 is validated, demonstrating that it activates the expression of a raffinose synthase gene, thereby increasing raffinose levels and conferring cold tolerance. Together, these augmented tools, the integrated data, and novel loci establish a better foundation for trait aggregation that will enhance breeding efficiency and boost the development of high‐quality grape varieties. Researchers develop advanced tools to study grapevine traits like berry quality and stress resilience. A 200K SNP array and high‐throughput phenotyping enable the identification of loci linked to berry shape, sugar content, acidity, and cold tolerance. Functional validation of genes such as NAC08 reveals roles in cold tolerance. These innovations improve breeding efficiency for high‐quality grapes.